ESG reporting : A Case Study - Vavrušková, Nela; Houska, Daniel; Patočka, Radim; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the compliance of a selected company's sustainability report with the European Sustainability Reporting Standards (ESRS). The literature review investigates the main drivers of ESG reporting, the impacts of ESG reporting on company performance and investors, and the risks and challenges of sustainability disclosure. Further, the literature review also covers the regulatory environment of ESG reporting in the European Union, including the related Corporate Sustainability Reporting Directive and the ESRS. The research focuses on gap analysis of sustainability report, identifying shortcomings and deviations from regulatory requirements. As a result of the research, compliance is assessed, and recommendations are formulated to increase the level of compliance
Vedoucí práce: Daniel Houska
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses